Boosted spatial charge carrier separation of binary ZnFe2O4/S-g-C3N4 heterojunction for visible-light-driven photocatalytic activity and antimicrobial performance - Iqbal, Shahid; Amjad, Adnan; Javed, Mohsin; Alfakeer, M.; Mushtaq, Muhammad; Rabea, Sameh; Elkaeed, Eslam B.; Pashameah, Rami Adel; Alzahrani, Eman; Farouk, Abd-ElAziem (Frontiers in Chemistry, 2022)
A potential method for removing toxins from contaminated wastewater, especially organic pollutants, is photo-catalysis. Here, a simple technique for producing zinc ferrite nanoparticles (ZnFe2O4 NPS) with varying quantities of sulphur doped graphitic carbon nitride nanocomposites (ZnFe2O4/S-g-C3N4 NCs) has been described. Then, using X-ray diffraction (XRD), TEM, EDX, XPS, photocurrent response, EIS, and Fourier Transform Infrared spectroscopy (FT-IR), the photo-catalytic activity of the produced nanoparticles (NPs) and nanocomposites (NCs) was examined and evaluated. The photo-catalytic activity of ZnFe2O4/S-g-C3N4 NCs was compared to a model pollutant dye, methylene blue, while degradation was evaluated spectrophotometrically (MB). Solar light has been used through irradiation as a source of lighting. The photocatalytic behaviour of the ZnFe2O4/S-g-C3N4 NCs photocatalyst was superior to that of genuine ZnFe2O4 and S-g-C3N4, which was attributed to synergic effects at the ZnFe2O4/S-g-C3N4 interconnection. Antimicrobial activity of ZnFe2O4/S-g-C3N4 against Gram-positive and Gram-negative bacteria under visible light was performed. In addition, these ZnFe2O4/S-g-C3N4 NCs show a lot of promise as an antibacterial agent.